Incidence and clearance of penile human papillomavirus infection among circumcised Kenyan men. (October 2020) - Backes, Danielle M; Bosire, Claire; Hudgens, Michael G; Fokar, Ali; Agot, Kawango; Opiyo, Felix; Moses, Stephen; Meijer, Chris JLM; Bailey, Robert C; Snijders, Peter JF; Smith, Jennifer S
Prospective data are limited on human papillomavirus (HPV) acquisition and clearance among circumcised men from resource-limited geographical regions, particularly Africa. The goal of this study was to estimate incidence and clearance of type-specific genital HPV infection in men. Penile exfoliated cell specimens were collected from the glans/coronal sulcus and shaft of 1, 037 circumcised Kenyan men at baseline and 6-, 12- and 18-month follow-up visits between 2003–2007. Specimens were tested with GP5+/6+ PCR to detect 44 HPV types. The median age of participants at baseline was 21 years (range 18–28). The 12- and 18-month incidence rates (IRs) for any HPV were 34.9/100 person-years (95% confidence interval [CI]: 31.2–39.0) and 36.4/100 person-years (95% CI: 32.9–40.2), respectively. The 18-month cumulative risk for high-risk HPV was 30% compared to 16% for low-risk HPV. Cumulative risk was not associated with age or anatomical site. The estimated probability of any HPV infection clearing by 12 months was 0.92. Time until HPV clearance was not associated with age, anatomical site, or whether HPV infection type was high-risk or low-risk. HPV IRs among circumcised men in this study were comparable to other circumcised populations.